The Role of the Pediatrician in Forming of the Parental Compliance for Influenza Vaccination - L. V. Kramar; A. B. Nevinsky (LLC "Diagnostics and Vaccines", 2015)
Based on the questioning of 160 people the social aspects of the formation of the parental compliance to immunize their children against influenza were studied. It was found that 96% of parents are aware of the possibility of preventing influenza by vaccination. However only 33.7% of them annually performed immunization. Among the reasons for failure of vaccination the most common is the fear of complications (38.9%), opinion about the poor quality of vaccines (25.8%), inefficiency of vaccines (19.6%). High social role of district pediatricians in formation of the parental compliance to immunize their children against influenza has been proven.